First record of males of Encentrum mucronatum Wulfert, 1936 and Encentrum martes Wulfert, 1939 (Rotifera: Dicranophoridae) including notes on males across Rotifera Monogononta - Riemann, Ole; Kieneke, Alexander (Zootaxa, 2008)
A detailed description is given of the males of Encentrum mucronatum Wulfert, 1936 and Encentrum martes Wulfert, 1939. The degree of miniaturisation relative to the corresponding females is assessed and compared to males in selected planktonic rotifers. Different degrees of miniaturisation are related to differences in population dynamics.